2020
DOI: 10.21580/jiemb.2020.2.1.7688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial literacy and financial efficacy on individual financial management

Abstract: Purpose – This study aims to determine the effect of financial literacy and financial efficacy on financial management.Method – Using mixed methods, namely quantitative and qualitative, this study managed to collect a sample of 307 respondents.Result – This research provides evidence that the level of a person's financial knowledge can affect his financial management as well as his financial satisfaction, with these results directly this research strengthens the evidence that gender does not affect financial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Financial capability encompasses knowledge, skills, and behaviors related to managing income and expenditure, directly influencing consumer financial satisfaction [81]. Saadah's [82] study revealed that financial literacy and efficacy are key factors in individual financial management, affecting financial satisfaction. In addition, financial management practices, including knowledge, attitude, and skills, significantly impact employees' financial management practices and satisfaction [83].…”
Section: Theme 5: Financial Management Skillsmentioning
confidence: 99%
“…Financial capability encompasses knowledge, skills, and behaviors related to managing income and expenditure, directly influencing consumer financial satisfaction [81]. Saadah's [82] study revealed that financial literacy and efficacy are key factors in individual financial management, affecting financial satisfaction. In addition, financial management practices, including knowledge, attitude, and skills, significantly impact employees' financial management practices and satisfaction [83].…”
Section: Theme 5: Financial Management Skillsmentioning
confidence: 99%
“…Salah satu indikator yang mempengaruhi financial wellbeing adalah efikasi keuangan atau kepercayaan diri mampu mengelola keuangan dengan baik (Saadah, 2020). Efikasi diri mengacu pada rasa keyakinan pribadi bahwa seseorang dapat menaklukkan dan berhasil di bawah tantangan hidup tertentu (Rothwell, Khan, & Cherney, 2016), sehingga efikasi keuangan adalah kemampuan bertindak untuk mengubah perilaku keuangan dengan kontrol dan pengendalian yang lebih bagus (Herawati et al, 2018).…”
Section: Pendahuluanunclassified
“…Memiliki ambisi, jiwa berkompetisi, tanggung jawab dipandang perlu jika ingin mendapatkan efikasi keuangan. Temuan ini sejalan dengan beberapa penelitian sebelumnya yaitu yang telah dilakukan oleh Brandon & Smith (2009), Saadah (2020), dan Woodyard & Robb (2012), sepakat bahwa efikasi keuangan memberikan kesempatan kepada pegawai untuk dapat lebih fleksibel dalam mengelola keuangannya.…”
Section: Tabel 3 Hasil Goodness Of Fit Modelunclassified
“…The halal industry has also helped broaden understanding and appreciation of Islamic culture and beliefs on a global level. By considering sharia principles and integrating them into various sectors, the halal industry also contributes positively to society and continues to experience development and the economy at large (Saadah, 2018) . In general, there are several sectors that are developing in the halal industry, namely the food, clothing, pharmaceutical, travel and tourism, media, cosmetics and finance sectors.…”
Section: Introductionmentioning
confidence: 99%